A COMPARISON OF SUSIE SALMON AND HANNAH BAKER’S CHARACTERS AS THE VICTIMS OF RAPE - Anastasia Amelia; Muhammad Natsir; Indah Sari Lubis (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
This research was aimed to analyze the main characters of two novels, which are Susie Salmon from The Lovely Bones novel (2002) by Alice Sebold, and Hannah Baker from Thirteen Reasons Why novel (2007) by Jay Asher. The purpose of the research was to found out the similarities and differences of both characters as the victims of rape through the characterization and plot development theories. The research used the qualitative method and content analysis. The results showed that both characters have similarities based on their characterization through the actions, speeches, and narration that showed them as smart girls. In the plot development, the similarities of both characters were found in the exposition. As the victims of rape, both characters reveal the reason for their death in exposition. In terms of differences, based on the characterization through their thought and action, Susie was showed as a confident and strong girl. While Hannah was showed as an introvert and weak girl in the plot development, the differences of both characters were found in the ending of the plot. As the victim of rape who did not survive, Susie finally let go of her regrets and chose to move on, while Hannah who can no longer bear the pain chose to end her life. The researcher suggests the next researcher to analyze the mental health of rape survivors and victims of bullying.